Systematics and evolutionary ecology of Osteospermum section Polygalinae DC - James, Lauren (Department of Biological Sciences, 2025)
Osteospermum L. (Asteraceae) is a genus of ca. 80 species of mainly yellow-flowered annual and perennial daisies, having most of its diversity in the Greater Cape Floristic Region of South Africa. The genus is characterised by remarkable variation in fruit structure and dispersal biology, putatively including species that employ myrmecochory (dispersal by ants). Myrmecochory is thought to be exceptionally prevalent in the species-rich Fynbos Biome and has gained interest as a possible driver of speciation due to short dispersal distances limiting gene flow and possible fitness advantages provided by seed deposition in ant nests. Due to its diversity of fruit types, Osteospermum provides an excellent system for the study of dispersal biology and its effect on diversification. However, the species-level taxonomy of Osteospermum has received little attention since it was last revised by Norlindh in 1943, with the current species concepts being ambiguous and possibly not representing evolutionary independent units and they are therefore inappropriate for testing evolutionary hypotheses. This study therefore first uses an integrative taxonomic approach to reassess the species-level taxonomy of Osteospermum section Polygalinae DC, a fynbos-centred group that contains a putatively myrmecochorous species, but within which species boundaries and relationships are especially unclear. The monophyly of O. sect. Polygalinae is confirmed using phylogenetic analysis of ETS and ITS sequences, while analysis of genomic (genotyping-by-sequencing, GBS), morphological and ecological data reveals O. sect. Polygalinae to comprise between 14 and 16 species, with well-resolved relationships. In the context of this revised species taxonomy and inferred phylogenetic tree, ancestral reconstructions of fruit traits are used, in conjunction with data from field experiments, to test the hypothesis of adaptation to ant dispersal. Myrmecochory, which is associated with the appearance of an elaiosome-like structure on the fruit, is found to have originated once, in O. corymbosum. The remaining species do not appear specifically adapted for dispersal, suggesting that they are passively dispersed. Field experiments confirm that elaiosomes in O. corymbosum attract ants and facilitate rapid transport of fruits underground. While previous studies suggest that myrmecochory stimulates diversification by reducing dispersal-mediated gene flow, a comparison of isolation-by-distance (IBD) based on GBS data finds limited support for this hypothesis, the IBD slope of O. corymbosum exceeding that of only four of the six species to which it was compared. Thus, the importance of myrmecochory as a driver of diversification in the Cape, as a consequence of a lower spatial scale of gene flow, may have been overstated. More importantly, perhaps, ant dispersal presents an important adaptation for avoiding predation during the inter-fire period and fire itself, which is critical in environments such as the Cape fynbos and may be particularly important for species that flower early in the inter-fire period.